Utilização de cinza de casca de arroz para remoção de hidrocarbonetos aromáticos em efluente petroquímico, através de um sistema de filtração com pressão positiva - Berwanger Filho, Jorge Augusto (Universidade do Vale do Rio dos Sinos, 2014)
The contamination of water by aromatic hydrocarbons (BTEX) causes negative environmental impacts. Petrochemical industrial wastewater generated from the processes of extracting oil contains such harmful pollutants to our health. Adsorption processes are widely used in the removal of BTEX in contaminated effluent, being the most popular activated carbon adsorbent. However the process of obtaining the activated carbon is complex and is potentially polluting. Researches involving the use of rice husk ash (RHA) as an adsorbent materials have been undertaken, however its effectiveness is directly related to the burning conditions (type of the reactor used, magnitude and the duration of exposure), as well as the type of pollutant, its solubility, pH and the concentration thereof. The research was conducted at the Laboratory of Materials Characterization in UNISINOS, a system of positive filtration bench was being used at a pressure of 4.5 kg.f/m², and three types of RHA from two distinct processes of generation of ashes, two achieved through the reactor grid-like and other by fluidized bed type reactor as a filtering medium. The RHAs were characterized through the trials of X-Ray Fluorescence, Grain Size Distribution, Fire Loss, X-ray diffraction, microscopy scanning electron, and the removal efficiency of pollutants (BTEX) verified by direct analysis of the results obtained by chromatography gas with detection by Flame Ionization. For each assay a mass of 45g as an alternative RHA adsorbent and 1 L of petrochemical industrial wastewater was used. According to the results, the RHA proved to be a good adsorbent for the removal of BTEX in petrochemical effluents with low concentrations (mg / l) of these contaminants resulting from reaching higher than 98% efficiency, however it was not possible to observe a trend in efficiency results probably due to the concentration range of BTEX contained in the effluent (mg/L), the losses by volatilization, by packing the ashes in the treatment system and column because it is a real effluent.
Keywords: Cinza de casca de arroz; Efluente petroquímico; BTEX; Adsorção; Rice husk ash; Petrochemical wastewater; Adsorption; ACCNPQ::Engenharias::Engenharia Civil